SUBJEKTIVITAS NOMADIK DALAM NOVEL GENTAYANGAN KARYA INTAN PARAMADITHA - Ramayda Akmal (20-87-2496)
This study aims to formulate construction of subjectivity that presented in the novel Gentayangan written by Intan Paramaditha. An analysis to the representation of the major components of subjectivity, such as the World, the Self and the Other is the mainstay of this process. Using the method of qualitative and descriptive analysis, and theoretical concepts on travel literature, subjectivity, and nomadic subject, this study concludes that the work has represented the subjectivity of nomadic woman; who is floating in the World, transcending the boundaries between the Self and the Other, and is between the desire to roam freely and to return home.